Malaysian management review
The Malaysian Management Review (MMR) is the academically referred and professional journal of the Malaysian Institute of Management (MIM). The mission of the MMR is to advance the state of the art of knowledge and practice in key areas of management and corporate leadership. As such, the MMR seeks to present both theoretical and practical knowledge that are useful to academicians, researchers and practitioners.